Association between heavy metals exposure (cadmium, lead, arsenic, mercury) and child autistic disorder: a systematic review and meta-analysis - Mengmeng Ding; Shanshan Shi; Shuyan Qie; Jinglu Li; Xiaoming Xi (Frontiers Media S.A., 2023)
BackgroundStudies have found that toxic heavy metals exposure could induce the generation of reactive oxygen species (ROS), and is of epigenetic effect, which might be associated with the occurrence of Autistic Disorder (ASD). This systematic review and meta-analysis aims to elucidate the association between exposure to 4 heavy metals, cadmium (Cd), lead (Pb), arsenic(As), and mercury (Hg), and the occurrence of ASD in children.MethodsWe searched PubMed, Web of Science, Embase, and Cochrane Library, from their inception to October 2022, for epidemiological investigations that explore the association between exposure to Cd, Pb, As, or Hg and the occurrence of child ASD.ResultsA total of 53 studies were included, involving 5,054 individuals aged less than 18 (2,533 ASD patients and 2,521 healthy controls). Compared with the healthy controls, in hair and blood tests, concentrations of the 4 heavy metals were significantly higher in the ASD group than in the healthy control group, and the differences in Pb, arsenic and Hg were statistically significant (P < 0.05). In the urine test, concentrations of arsenic and Hg were significantly higher in the ASD group than in the healthy control group (P < 0.05), while the results of Cd and Pb were opposite to those of arsenic and Hg (P > 0.05). Subgroup analysis for geographic regions showed that ASD patients in Asia and Europe had higher concentrations of the 4 heavy metals, compared with the healthy controls, in which the differences in Pb, arsenic, and Hg were statistically significant (P < 0.05), while in North America, the healthy controls had higher Cd, arsenic, and Hg concentrations (P > 0.05).ConclusionCompared with the healthy control group, the ASD group had higher concentrations of Cd, Pb, arsenic, and Hg. These 4 heavy metals play different roles in the occurrence and progression of ASD. Moreover, there is significant heterogeneity among the included studies due to controversies about the study results among different countries and regions and different sources of detection materials. The results of this study firmly support the policies to limit heavy metals exposure, especially among pregnant women and young children, so as to help reduce the incidence of ASD.